The Effect of Psychological Capital and Emotional Labor on Job Performance: A Study on Five Star Hotel Enterprises in Antalya - Neslihan Kan Sonmez (Istanbul Business Research (IBR), 2021)
Service quality and customer satisfaction, which are basic goals of hotel enterprises, can be achieved by the high job performance of qualified staff. The focal point of this study was the key role that psychological capital and emotional labor play in high job performance. In this study, which aimed to determine the effect of psychological capital and emotional labor on job performance, the sample group consisted of 400 personnel employed by 16 five-star hotel enterprises operating in the centre of Antalya, specifically in the districts of Kemer and Alanya. The data collected by questionnaire technique were analysed by statistical techniques, such as frequency and percentage distribution, arithmetic mean, standard deviation, Pearson's correlation analysis, multiple linear regression analysis, independent samples t-test, and one-way analysis of variance. What is more, a factor analysis was administered for validity and reliability, and Cronbach's Alpha coefficients were calculated. Obtained data suggested that the psychological capital levels of employees were positive above the medium level. The general emotional labor performance of employees was at the medium level. The job performance levels perceived by employees were high. As a result of the correlation analysis performed in the study, positive correlations were identified between psychological capital and emotional labor at r=0.529, psychological capital and job performance at r=0.717, and emotional labor and job performance at r=0.595. The regression analysis showed that one unit of change in the psychological capital caused an increase of 0.543 on the job performance, and a change of one unit in the psychological capital resulted in an increase of 0.712 on the job performance. In addition, according to the t-test and variance analysis results, while psychological capital, emotional labor, and job performance did not differ significantly according to gender, marital status, age, or education level, psychological capital levels of the hotel employees differed significantly according to their departments, and emotional labor performance differed significantly in line with their departments and working durations.
Keywords: 650; Psychological Capital; Emotional Labor; Job Performance; Hotel Enterprises